The Great Disorder: A Review of the Book of that Title by Gerald D. Feldman - Kindleberger, Charles P. (Journal of Economic Literature, 1994)
A MONG THE BIG unsettled questions of modrem history and economic history, four loom large-the industrial revolution, the French revolution, the German inflation of the 1920s, and the world depression of the 1930s. All are still studied, debated giving rise to many theories, mostly mono-causal and conflicting. More unsettled questions may be on the way, for example the inflation of the 1980s and the stagnation of the early 1990s. But Gerald Feldman has written a big book that must be taken into account in any discussion of the German inflation, big in many senses, 1000 pages of double-column print (triple columns in the index), 4.48 pounds in weight at my local supermarket, and covering in the order of the subtitle the politics, economics, and sociology of this pathological episode. Specialists in any one discipline may find their own discipline relatively neglected, especially economists who tend to want more theory, as D. C. Coleman indicates, who asserts that theories are what economists make, while historians need evidence (1969, p. 8). The evidence here is prodigious: 49 tables, two-thirds that number of photographs and illustrations, 85 pages of endnotes, 24 pages of bibliography, and a 42-page index, the work of 15 years of study of the subject and 43 earlier publications of Feldman-books, articles, and edited work, some with colleagues, mostly his own. The feast is rich; some economists and economic historians may find it too rich for ready digestion. Feldman is aware of his problem in combining contradictory modes of analysis, but believes it necessary. Partly in a reaction to the work of Carl-Ludwig Holtfrerich whose The German Inflation, 1914-1923 (1986) concludes that the results of the inflation on balance were favorable in giving Germany years of investment and full employment in a largely depressed world and ridding it of private foreign and all internal debt, he asserts: